The Female FTSE Board Report 2020: Taking Targets Seriously - Vinnicombe, Susan; Doldor, Elena; Battista, Valentina; Tessaro, Michelle (Cranfield University, 2020)
This year we see a positive picture in terms of the number of women on corporate boards. The percentage of women on FTSE 100 boards is 34.5% and the equivalent figure for FTSE 250 boards is 31.9%, so hopefully all FTSE 350 boards should hit the Hampton-Alexander target of 33% by the end of 2020. In total 324 women hold 355 FTSE 100 directorships. The percentage of female non-executive directors (NEDs) is at an all-time high of 40.8%, whilst the percentage of female executive directorships has risen slightly this year to 13.2%. There has been more progress recorded on the FTSE 250 boards, where the percentage of female NEDs is 37.6% and the percentage of female executive directors (EDs) is 11.3%. There is quite a lot of variance across boards indicating that only 63% FTSE 100 and 53% FTSE 250 have reached the target of 33% women in their boards.